Electronic Cigarette Use Prevalence, Associated Factors, and Pattern by Cigarette Smoking Status in the United States From NHANES (National Health and Nutrition Examination Survey) 2013–2014. Issue 14 (17th July 2018) - Jaber, Rana M.; Mirbolouk, Mohammadhassan; DeFilippis, Andrew P.; Maziak, Wasim; Keith, Rachel; Payne, Thomas; Stokes, Andrew; Benjamin, Emelia; Bhatnagar, Aruni; Blankstein, Ron; Saxena, Anshul; Blaha, Michael J.; et al.
Abstract : Background: To examine the prevalence and patterns of recent electronic cigarette (e‐cigarette) use in a nationally representative sample of US adults and adolescents. Methods and Results: Using tobacco information from NHANES (National Health and Nutrition Examination Survey) 2013–2014, 5423 adults and 895 adolescents (aged 13–17 years) were included in this analysis. Demographic, tobacco use, and drug use information were self‐reported. Recent e‐cigarette use (within the previous 5 days) was stratified by smoking status. Of 125 e‐cigarette users, 116 participants were aged ≥18 years, corresponding to 2.6% (95% confidence interval [CI], 2.0–3.1) and 1.21% (95% CI, 0.3–2.1) prevalence of e‐cigarette use among US adults and adolescents, respectively. E‐cigarette adult users were current smokers (68.1%), former smokers (23.7%), and never smokers (8.2%). The highest prevalence of e‐cigarette use was among current smokers (8.2%; 95% CI, 6.3–10.1), followed by former smokers (2.7%; 95% CI, 1.4–4.1), and then never smokers (0.4%; 95% CI, 0.2–0.6). After adjusting for age, sex, and ethnicity, e‐cigarette users had higher odds of being exposed to secondhand smoke (odds ratio: 6.3; 95% CI, 3.6–11.1) and drinking alcohol (odds ratio: 4.2; 95% CI, 1.8–10.0) and lower odds of having at least a college education or a higher income, compared with tobacco nonusers. Conclusions: Between 2013 and 2014, e‐cigarette use in the United States was more common among younger people, those with low socioeconomic status, and current and former smokers. These findings will help inform future research as well as public policy and regulatory actions.